Filmowa Łódź w oczach studentów i profesorów PWSFTViT - Hendrykowski, Marek (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2013)
Cinematic City Łódź through eyes of the Film School. Students and Professors Łódź is often called “the capital of Polish film”. The cultural history of this town from the end of World War Two to the present day is closely connected with the movie industry. Marek Hendrykowski’s study on Łódź as a cinematic city offers the first comprehensive critical guide to the many films, interviews, published writings and individual memoirs of the Film School’s students and professors. This panoramic view presents the process of the historical transformation of cinematic images from Łódź between 1945 and 2013, as well as the profound influence this town had on many filmmakers. It serves as a reference work that will allow readers to navigate the subject’s wide range of examples: from Antoni Bohdziewicz, Jerzy Bossak, Kazimierz Kutz and Andrzej Wajda to Krzysztof Kieślowski, Wojciech Wiszniewski, Janusz Kijowski and Polish filmmakers of new generation.